Antifogging resin sheet and secondary molded product thereof
Patent Information
- Application Number
- JP2023130774
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-21
AI Technical Summary
【0010】 本発明により、良好な防曇性を示しつつ、防曇層と熱可塑性樹脂シートとの密着性に優れ、防曇層が熱可塑性樹脂シートから剥がれにくく、防曇効果発現後に水滴痕も見られない防曇性樹脂シートを提供することができる。
Smart Images

Figure 2025025714000001 
Figure 2025025714000002 
Figure 2025025714000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an anti-fogging resin sheet for use in food packaging containers and various other containers, and to a secondary molded product thereof. [Background technology]
[0002] Resin sheets extruded from various thermoplastic resins are heated and molded into secondary forms using a vacuum forming machine, a compressed air vacuum forming machine, a hot plate compressed air forming machine, etc., and the secondary molded products obtained are widely used for packaging lightweight food packaging containers and other items. Among these resin sheets, transparent resin sheets such as polystyrene, polyethylene terephthalate, polypropylene, etc. are widely used as lid materials for lunch boxes, side dish containers, etc., due to their transparency. However, these lid materials have a problem in that the inner surface of the lid material becomes cloudy due to water vapor generated from the contents.
[0003] As a means for solving the above problems, for example, an anti-fogging styrene-based resin sheet has been proposed in which an anti-fogging agent consisting of a sucrose fatty acid ester, polyvinyl alcohol, and a fatty acid salt is applied onto a styrene-based resin sheet (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2008-222868 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present inventors have evaluated anti-fog resin sheets obtained by applying an anti-fog agent onto a thermoplastic resin sheet such as a styrene-based resin sheet as described in the above Patent Document 1. As a result, as shown in the following Comparative Example, it was found that an anti-fog resin sheet having an anti-fog layer formed on a thermoplastic resin sheet, the anti-fog layer being made of an anti-fog agent containing a sucrose fatty acid ester, polyvinyl alcohol, and a fatty acid salt having 12 carbon atoms, has a problem in that the adhesion between the anti-fog layer and the thermoplastic resin sheet is poor and the anti-fog layer is easily peeled off from the thermoplastic resin sheet.
[0006] Furthermore, if water droplets are visible after the anti-fog effect has been exerted, the appearance of the molded article will deteriorate. Therefore, in order to produce molded articles with good appearance, an anti-fog resin sheet that does not show water droplets after the anti-fog effect has been exerted is desired.
[0007] Therefore, an object of the present invention is to provide an anti-fog resin sheet which exhibits good anti-fog properties, has excellent adhesion between the anti-fog layer and the thermoplastic resin sheet, and the anti-fog layer is not easily peeled off from the thermoplastic resin sheet, and further has satisfactory performance in that no water droplet marks are visible after the anti-fog effect is exerted. [Means for solving the problem]
[0008] As a result of intensive research into solving the above problems, the present inventors have found that when an anti-fog resin sheet is formed using an anti-fog agent containing a fatty acid salt (A) including a laurate salt and at least one type (B) selected from polyvinyl alcohol and polyvinylpyrrolidone, but not containing a sucrose fatty acid ester, an anti-fog resin sheet can be obtained which exhibits good anti-fog properties, has excellent adhesion between the anti-fog layer and the thermoplastic resin sheet, is not easily peeled off from the thermoplastic resin sheet, and shows no water droplet marks after the anti-fog effect is exerted, thereby completing the present invention.
[0009] That is, the present invention includes the following aspects. [1] At least one surface of a thermoplastic resin sheet, The anti-fogging resin sheet has an anti-fogging layer formed thereon, the anti-fogging agent comprising (A) a fatty acid salt including a laurate salt, and (B) at least one selected from polyvinyl alcohol and polyvinylpyrrolidone, but not including a sucrose fatty acid ester. [2] The anti-fog resin sheet according to [1], wherein the laurate is at least one selected from sodium laurate and potassium laurate. [3] The anti-fog resin sheet according to [2], wherein the laurate is potassium laurate. [4] The anti-fog resin sheet according to any one of [1] to [3], wherein the polyvinyl alcohol (B) has a saponification degree of 65 to 90 mol %. [5] The anti-fog resin sheet according to any one of [1] to [4], wherein a release layer made of silicone oil (E) is formed on the other side of the thermoplastic resin sheet opposite to the side on which the anti-fog layer is provided. [6] The anti-fog resin sheet according to any one of [1] to [5], wherein the thermoplastic resin sheet is a styrene-based resin sheet. [7] A secondary molded product obtained by molding the anti-fog resin sheet according to any one of [1] to [6]. Effect of the Invention
[0010] The present invention can provide an anti-fog resin sheet that exhibits good anti-fog properties, has excellent adhesion between the anti-fog layer and the thermoplastic resin sheet, the anti-fog layer is not easily peeled off from the thermoplastic resin sheet, and no water droplet marks are visible after the anti-fog effect is exerted. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below. Note that the following description of the constituent elements is merely an example for explaining the present invention, and the present invention is not limited to these contents.
[0012] (Anti-fogging resin sheet) The anti-fog resin sheet of the present invention has a thermoplastic resin sheet and an anti-fog layer. The anti-fogging layer is formed on at least one surface of the thermoplastic resin sheet. The anti-fogging layer is formed using an anti-fogging agent. The anti-fogging resin sheet of the present invention may further have a release layer. The release layer is preferably formed on the other surface of the thermoplastic resin sheet opposite to the surface on which the anti-fogging layer is provided.
[0013] <Thermoplastic resin sheet> The type of resin for the thermoplastic resin sheet serving as the substrate of the anti-fog resin sheet of the present invention is not particularly limited, but is preferably transparent, and examples thereof include styrene-based resins such as polystyrene, crystalline polystyrene, styrene-butadiene copolymer, styrene-isoprene-styrene copolymer, styrene-isoprene-butadiene-styrene copolymer, styrene-ethylene-butadiene-styrene copolymer, transparent styrene-butadiene-(meth)acrylic acid alkyl ester copolymer, styrene-(meth)acrylic acid copolymer, styrene-maleic anhydride copolymer, and styrene-(meth)acrylic acid alkyl ester copolymer; propylene-based resins such as polypropylene, propylene-butadiene copolymer, and ethylene-propylene copolymer; polycarbonate, polyvinyl chloride, polyvinylidene chloride, polyamide resins such as nylon 6, and polyester resins such as polyethylene terephthalate are preferred.
[0014] In addition, two or more of these resins may be mixed and used as long as the transparency of the anti-fog resin sheet of the present invention is not impaired. Furthermore, these thermoplastic resin sheets may be multi-layered sheets of two or more layers using one or more of these resins. Furthermore, these thermoplastic resin sheets may be subjected to uniaxial or biaxial stretching treatment.
[0015] Furthermore, biaxially oriented polystyrene resin sheets are often heated and molded using a hot plate compressed air molding machine, and in this case, when a conventional antifogging agent is used, the antifogging property of the molded body during heating and molding tends to decrease significantly. However, in the antifogging resin sheet of the present invention, even when a biaxially oriented polystyrene resin sheet is used as the substrate, a secondary molded product having excellent antifogging property can be obtained. From the viewpoint of compatibility with a general-purpose hot plate compressed air molding machine, a polystyrene resin sheet is preferred as the substrate for the antifogging resin sheet of the present invention, and a biaxially oriented polystyrene resin sheet is most preferred.
[0016] The thickness of these thermoplastic resin sheets is not particularly limited, but is preferably 0.05 to 1.0 mm from the viewpoint of the rigidity and strength of the secondary molded product when the anti-fogging resin sheet is secondary molded.
[0017] In the resins used for these thermoplastic resin sheets, various fine particles for producing protrusions on the surface of the resin sheet can be added to prevent blocking of the anti-fog resin sheet, within a range that does not impair the transparency of the resin sheet. Examples of the fine particles include resin crosslinked beads such as styrene-based resin crosslinked beads, (meth)acrylic acid ester-based resin crosslinked beads, and polyurethane-based resin crosslinked beads, inorganic fine particles such as silica, hydrophobized silica, spherical silica, soft calcium carbonate, titanium oxide, and talc, and rubber fine particles. For rubber fine particles, a method of using a rubber-containing resin in combination is exemplified. The rubber-containing resin used here is different from the thermoplastic resin that is the base material of the anti-fogging resin sheet, and examples of the rubber-containing resin include high impact polystyrene (HIPS), styrene-acrylonitrile-butadiene copolymer (ABS), styrene-ethylene-butadiene-styrene copolymer (SEBS), styrene-butadiene-(meth)acrylic acid ester copolymer (MBS), and high impact (meth)acrylic acid ester (HI-PMMA).
[0018] <Anti-fogging layer> The anti-fogging layer is formed using an anti-fogging agent. The antifogging agent contains (A) a fatty acid salt including a laurate salt, and (B) at least one selected from polyvinyl alcohol and polyvinylpyrrolidone, but does not contain a sucrose fatty acid ester.
[0019] <<Fatty acid salts including laurate (A)>> In the present invention, the fatty acid salt (A) containing a laurate is defined. In the present invention, so long as the composition contains a laurate, it may contain a fatty acid salt other than the laurate. Here, the fatty acid other than lauric acid may be a saturated fatty acid or an unsaturated fatty acid, and examples thereof include saturated fatty acids such as caproic acid, caprylic acid, myristic acid, palmitic acid, and stearic acid, and unsaturated fatty acids such as oleic acid, linoleic acid, and linolenic acid.
[0020] The proportion of lauric acid in all fatty acids may be, for example, 40% by mass or more, 45% by mass or more, 47% by mass or more, 50% by mass or more, or 70% by mass or more, or 100% by mass of lauric acid.
[0021] Examples of the fatty acid salt include sodium salts and potassium salts. From the viewpoint of antistatic effect, potassium salts are more preferable than sodium salts.
[0022] Examples of the laurate salt include sodium laurate and potassium laurate. The laurate salt in the present invention is, for example, at least one selected from sodium laurate and potassium laurate. Sodium laurate and potassium laurate (A) are known as anionic surfactants, and in the present invention, commercially available products can be used. In the present invention, of sodium laurate and potassium laurate, potassium laurate is particularly preferred from the viewpoint of antistatic effect.
[0023] <<Polyvinyl alcohol (B) and / or polyvinylpyrrolidone (B)>> <<<Polyvinyl alcohol (B)>>> The polyvinyl alcohol (also called PVA) (B) is a homopolymer consisting of vinyl alcohol units or a copolymer consisting of vinyl alcohol units and vinyl acetate units, and the content of vinyl alcohol units is 50% by mass or more. The polyvinyl alcohol (B) is preferably a partial saponification reaction product of polyvinyl acetate, preferably having a saponification degree of 65 to 90 mol%, more preferably having a saponification degree of 70 to 90 mol%, and even more preferably having a saponification degree of 80 to 90 mol%. The preferred saponification degree is determined from the viewpoint of obtaining a significant antifogging improvement effect and not deteriorating the appearance of the antifogging resin sheet, and for example, by making the saponification degree 65 mol% or more, the water solubility is improved, and when the antifogging agent coating is formed by coating an aqueous solution, the dispersion uniformity of polyvinyl alcohol in the coating can be improved. Also, by making the saponification degree 90 mol% or less, the antifogging property becomes good. The viscosity of a 4% by mass aqueous solution of polyvinyl alcohol (B) at 20° C. is preferably 2 to 30 mPa·s, more preferably 2 to 25 mPa·s, even more preferably 4 to 15 mPa·s, even more preferably 4 to 9 mPa·s, particularly preferably 4 to 8 mPa·s, and particularly more preferably 4.5 to 6.0 mPa·s. From the viewpoints of obtaining an anti-fogging property improving effect and ease of mixing with an oleate, the viscosity of polyvinyl alcohol is preferably 2 mPa·s or more and 30 mPa·s or less, as described above.
[0024] <<<Polyvinylpyrrolidone (B)>>> The weight average molecular weight (Mw) of polyvinylpyrrolidone (B) is not particularly limited, but is preferably within the range of 8,000 to 3,000,000, more preferably within the range of 20,000 to 2,000,000, even more preferably within the range of 40,000 to 2,000,000, even more preferably within the range of 500,000 to 2,000,000, and particularly preferably within the range of 500,000 to 1,500,000. Within the range of 8,000 to 3,000,000, the smaller the weight average molecular weight of polyvinylpyrrolidone is, the easier it is to mix with an oleate salt, and the larger the weight average molecular weight is, the higher the heat resistance can be obtained.
[0025] The polyvinylpyrrolidone may be a commercially available product, and the commercially available product of polyvinylpyrrolidone may be in the form of a powder or a solution. In addition, for example, two or more kinds of polyvinylpyrrolidone having different weight average molecular weights may be used in combination.
[0026] Polyvinylpyrrolidone is typically a polymer composed of vinylpyrrolidone alone, but may be a copolymer of vinylpyrrolidone and other monomers as long as the effect of the present invention is not impaired. Examples of other monomers include acrylic acid esters, acrylic acid, methacrylic acid esters, methacrylic acid, styrene, vinyl acetate, etc. Polyvinylpyrrolidone may also be a block polymer or a graft polymer composed of a vinylpyrrolidone block and a polyvinyl alcohol block of another monomer.
[0027] <<Non-containing sucrose fatty acid ester>> As shown in the comparative examples below, in an anti-fog resin sheet in which an anti-fog layer made of an anti-fog agent containing a sucrose fatty acid ester, polyvinyl alcohol, and a fatty acid salt having 12 carbon atoms is formed on a thermoplastic resin sheet, the adhesion between the anti-fog layer and the thermoplastic resin sheet is poor, and the anti-fog layer is prone to peeling off from the thermoplastic resin sheet. Therefore, the antifogging agent of the present invention does not contain or substantially does not contain sucrose fatty acid esters. Substantially not containing means that the content of sucrose fatty acid esters is less than 10 ppm, which is the lower limit of general measurement, for example, when the content of sucrose fatty acid esters is measured using a (high performance liquid chromatography) measurement method. Here, the sucrose fatty acid ester includes those obtained by transesterification of sucrose with a lower alcohol ester of a fatty acid, such as a fatty acid methyl ester. Specific examples include sucrose stearate, sucrose palmitate, sucrose laurate, and sucrose oleate.
[0028] The antifogging agent according to the present invention contains (A) a fatty acid salt including a laurate and (B) at least one selected from polyvinyl alcohol and polyvinylpyrrolidone, but does not contain a sucrose fatty acid ester. In a mixed system of sucrose fatty acid ester and sodium laurate, or a mixed system of sucrose fatty acid ester and potassium laurate, the adhesion between the anti-fog layer applied to the thermoplastic resin sheet and the thermoplastic resin sheet is poor. For example, when the thermoplastic resin sheet is rolled up, the anti-fog agent is transferred to the opposite side, causing problems such as reduced transparency and poor anti-fog properties due to surface roughness of the coating film. However, the present invention can effectively prevent such problems. In the present invention, the composition used as the anti-fog agent contains fatty acid salt (A) including laurate salts such as sodium laurate and potassium laurate, which are highly water-soluble, so that the handling property during coating is good and the coating layer can be formed in good condition. It is believed that the formation of the coating layer in good condition also contributes to the maintenance and improvement of the anti-fog property of the anti-fog resin sheet. In addition, the anti-fog resin sheet of the present invention contains laurates such as sodium laurate and potassium laurate, and therefore exhibits an excellent effect in suppressing water droplet marks after the anti-fog effect is exerted. As shown in the following examples, the anti-fog resin sheet of the present invention is a resin sheet on which water droplet marks are not observed after the anti-fog effect is exerted. It is believed that the fatty acid lauric acid is more effective at suppressing water stains after the anti-fogging effect is exerted than that of oleic acid. Therefore, the anti-fogging resin sheet of the present invention, which contains a laurate such as sodium laurate or potassium laurate as an essential component, is more excellent in suppressing water stains after the anti-fogging effect is exerted.
[0029] The content of the fatty acid salt (A) according to the present invention is preferably 0.1 to 10 parts by mass, and more preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the aqueous solution containing the antifogging agent of the present invention. The content of the laurate salt according to the present invention is preferably 0.01 to 10 parts by mass, and more preferably 0.01 to 5 parts by mass, relative to 100 parts by mass of the aqueous solution containing the antifogging agent of the present invention. The content of the polyvinyl alcohol and / or polyvinylpyrrolidone (B) according to the present invention is preferably 0.05 to 20 parts by mass, and more preferably 0.05 to 10 parts by mass, relative to 100 parts by mass of the aqueous solution containing the antifogging agent of the present invention.
[0030] The content ratio of the fatty acid salt containing laurate (A) and the polyvinyl alcohol and / or polyvinylpyrrolidone (B) in the antifogging agent according to the present invention is preferably 5 parts by mass to 95 parts by mass:95 parts by mass to 5 parts by mass, more preferably 15 parts by mass to 85 parts by mass:85 parts by mass to 15 parts by mass, and even more preferably 15 parts by mass to 75 parts by mass:85 parts by mass to 25 parts by mass. In particular, in the present invention, it is more preferable from the viewpoint of improving anti-fogging properties that the composition used as the anti-fogging agent contains a relatively high proportion of a highly water-soluble laurate, and from the viewpoint of the appearance of the sheet after application, it is preferable that the composition contains a relatively low proportion of the laurate. For example, it is preferable that the fatty acid salt containing laurate (A):polyvinyl alcohol and / or polyvinylpyrrolidone (B)=15 parts by mass:85 parts by mass to 68 parts by mass:32 parts by mass. In the present invention, when both polyvinyl alcohol and polyvinylpyrrolidone are contained as component (B), the content of component (B) is the total amount of both of them added together.
[0031] <Release layer> In the present invention, a release layer can be formed by applying a release agent to the surface of the thermoplastic resin sheet opposite to the surface on which the anti-fogging layer is provided. As the release agent, silicone oil (E) can be used. From the viewpoints of safety and economy, this silicone oil (E) has a viscosity of 1,000,000 to 500,000 mm at 25°C. 2 Dimethylpolysiloxanes in the range of 1 / s are preferred.
[0032] In addition, when applying the silicone oil (E) to the surface of the thermoplastic resin sheet, it is preferable to use it in the form of a silicone emulsion. The average particle size of the silicone oil (E) in the silicone emulsion is preferably 1 μm or less. That is, if the average particle size exceeds 1 μm, it is difficult to apply the silicone oil uniformly, and the appearance of the anti-fog resin sheet is deteriorated.
[0033] In addition, the silicone oil (E) used in the present invention is preferably applied to the other side of the surface coated with the antifogging agent, since the appearance of the sheet or secondary molded product is improved. That is, when the silicone oil (E) is mixed and applied in the antifogging agent, there is a problem that the appearance of the sheet or secondary molded product is deteriorated, so the amount of silicone oil (E) needs to be 10.0 parts by mass or less for 100 parts by mass of the aqueous solution containing the antifogging agent of the present invention. Furthermore, it is preferable to make it 5.0 parts by mass or less, and it is particularly preferable that the antifogging agent does not contain silicone oil.
[0034] Furthermore, it is also possible to add a surfactant having an antistatic effect, a lubricant, etc. to the silicone emulsion liquid containing the silicone oil (E) used in the present invention.
[0035] <Method for manufacturing anti-fogging resin sheet> The method for producing the anti-fogging resin sheet of the present invention involves, for example, applying a solution of an anti-fogging agent (anti-fogging composition) containing a fatty acid salt (A) including a laurate salt and at least one type (B) selected from polyvinyl alcohol and polyvinylpyrrolidone, but not containing a sucrose fatty acid ester, to at least one surface of a thermoplastic resin sheet, and then drying the solvent to form an anti-fogging layer.
[0036] The method for producing the anti-fog resin sheet of the present invention is not particularly limited, but it is preferable to apply an anti-fog agent consisting of an aqueous solution to at least one surface of a thermoplastic resin sheet obtained by forming a film from a thermoplastic resin by a known method. Specifically, there can be mentioned a method in which one surface of a thermoplastic resin sheet is subjected to a hydrophilization treatment, and then the anti-fog agent of the present invention is applied to this treated surface, and the solvent is dried to form an anti-fog layer.
[0037] The method for applying the anti-fog agent used in the manufacturing method of the anti-fog resin sheet of the present invention includes known methods such as a spray coater, roll coater, gravure roll coater, knife coater, air knife coater, rotor dampening coater, and applicator system, and is not particularly limited.
[0038] The coating amount of the antifogging agent in the antifogging resin sheet of the present invention is preferably adjusted to a predetermined amount in order to improve the antifogging effect and prevent poor appearance due to uneven coating. Specifically, the coating amount of the solid content after drying, that is, the mass of the antifogging layer per unit area of the antifogging resin sheet, is 5 to 1,000 mg / m. 2 is preferably 5 to 150 mg / m 2 It is particularly preferred that:
[0039] Quantitative analysis of the amount of anti-fog agent applied can be performed by Fourier transform infrared spectrophotometer analysis (multiple internal reflection method) [FTIR analysis (ATR method)].
[0040] In addition, examples of the method for hydrophilizing the surface of the thermoplastic resin sheet include known methods such as acid treatment, flame treatment, and corona treatment. The surface of the thermoplastic resin sheet subjected to such hydrophilization treatment preferably has a wet tension of 38 mN / m or more, and more preferably has a wet tension of 45 to 60 mN / m in order to uniformly apply the antifogging agent and obtain a sufficient antifogging effect. Here, the wet tension is a value measured by the method described in JIS K6768-1999.
[0041] (Secondary molded product) By molding the anti-fogging resin sheet of the present invention by means of vacuum forming, compressed air vacuum forming, hot plate compressed air forming, or the like, it is possible to produce secondary molded products suitable for food containers such as lunch containers, side dish containers, sushi containers, and sashimi containers, particularly anti-fogging transparent lids for such food containers. EXAMPLES
[0042] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.
[0043] Example 1 1.7 mass % of sodium laurate and 1.7 mass % of polyvinyl alcohol (saponification degree 74 mol %, viscosity of 4% aqueous solution at 20°C 4.7 mPa·s) were mixed and dissolved in 96.8 mass % of water to obtain an anti-fogging agent (1).
[0044] Next, one side of a 0.21 mm thick biaxially oriented polystyrene resin sheet (Sandic Sheet 510, manufactured by Sandic Co., Ltd.) that had not been subjected to any coating treatment on its surface was subjected to a corona treatment with a wetting tension of 50 mN / m, and an anti-fog agent was applied to the corona-treated surface in a solid content of 50 mg / m using a roll coater method. 2 The anti-fogging agent (1) was appropriately diluted with water so as to obtain an anti-fogging resin sheet (1) having an anti-fogging layer formed on a polystyrene resin sheet, and then dried with a dryer. The amount of anti-fog agent applied was determined by measuring the infrared absorption spectrum of the sheet surface by the multiple internal reflection method (ATR method) using a Fourier transform infrared spectrophotometer (FTIR), and performing quantitative analysis based on a calibration curve created from standard samples with known application amounts.
[0045] The obtained anti-fog resin sheet (1) was evaluated for sheet appearance, anti-fog properties, adhesion to a sheet, presence or absence of water droplets, and antistatic properties according to the following methods.
[0046] (Evaluation of Appearance of Anti-Fog Resin Sheet) The sheet after application of the antifogging agent was visually observed to evaluate the presence or absence of whitening of the sheet. The lower the degree of whitening of the sheet, the better the appearance of the antifogging resin sheet. [Evaluation Criteria] ○: The sheet after application does not turn white and maintains transparency. △: The sheet after application is slightly whitened, but at a level that does not interfere with practical use. ×: The sheet after application was whitened and the transparency was significantly reduced.
[0047] (Evaluation of anti-fogging properties of secondary molded products) The anti-fogging resin sheet (1) was molded using a hot plate compressed air molding machine with a hot plate temperature of 125° C. and a mold shown below to obtain a secondary molded product (1). Mold: 94mm (length) x 94mm (width) x 30mm (depth), corners: 2R Next, in order to evaluate the anti-fogging properties assuming the case where the contents are observed from the outside when used in a high-temperature food container, the high-temperature anti-fogging properties of the secondary molded product were evaluated as follows. That is, a base material (obtained by secondary molding of a thermoplastic resin sheet) having the same shape as the secondary molded product was prepared, and a paper with a 15 mm square checkerboard pattern printed thereon was placed on it. Then, 100 mL of hot water at 90°C was poured into the base material, and the top of the base material was covered with the secondary molded product obtained in the above example. The upper part of the base material was then left at 23°C for 5 minutes, and the distortion of the checkerboard pattern visible through the secondary molded product and the degree of water droplets attached to the top surface and the inside of the four corners were visually observed. The less the secondary molded product is clouded, or the less the checkerboard pattern is visually distorted, the better the anti-fogging properties of the anti-fogging resin sheet. [Evaluation Criteria] ◎: The secondary molded product is not cloudy, and the checkerboard pattern is visible without distortion over 85% or more of the secondary molded product. ○: The secondary molded product is not cloudy, and the checkerboard pattern is visible without distortion over 50% or more of the area of the secondary molded product. △: The secondary molded product is not cloudy, but the checkerboard pattern appears distorted over an area larger than 15% of the secondary molded product. ×: Small water droplets adhere to the top surface or four corners of the secondary molded product, making it cloudy.
[0048] (Evaluation of adhesion between anti-fog agent and sheet) The adhesion between the anti-fogging layer made of the anti-fogging agent and the thermoplastic resin sheet (also referred to as the adhesion of the anti-fogging agent to the sheet) was evaluated. The surface of the anti-fogging resin sheet (1) was rubbed with a finger, and the presence or absence of peeling of the anti-fogging agent and the presence or absence of clouding of the sheet were evaluated. [Evaluation Criteria] 〇: The anti-fog agent does not peel off and the sheet does not become cloudy. △: There is a small amount of peeling of the anti-fog agent, but it is at a level that does not interfere with practical use. ×: The anti-fog agent peeled off from the sheet, and the sheet became cloudy.
[0049] (Evaluation of water droplets after anti-fog effect appears) After the anti-fogging test, water droplets on the secondary molded product were visually confirmed. [Evaluation Criteria] ◎: No water droplets are visible ○: There are a few water droplets, but they are almost non-existent. △: A few water droplets are visible, but not to the extent that it interferes with practical use. ×: Water droplets are white and noticeable, and the appearance of the molded product is deteriorated.
[0050] (Evaluation of antistatic properties) The surface resistance of the antifogging agent-coated surface of the antifogging resin sheet (1) was measured using a microcurrent meter manufactured by Advantest Corporation. [Evaluation Criteria] ○: Surface resistance less than 1.0×E+13Ω △: Surface resistance 1.0×E+13Ω or more and less than 1.0×E+15Ω ×: Surface resistance 1.0×E+15Ω or more
[0051] The evaluation results of Example 1 are shown in Table 1. The anti-fogging resin sheet (1) had good sheet appearance, anti-fogging properties, and adhesion, and no water droplet marks were observed after the anti-fogging properties were exhibited. In Table 1, since the content of sodium laurate is 1.7% by mass and polyvinyl alcohol is 1.7% by mass, sodium laurate is expressed as 1.7 / (1.7+1.7)=50 (% by mass) and polyvinyl alcohol is also expressed as 1.7 / (1.7+1.7)=50 (% by mass) (the same notation is used for other Examples and Comparative Examples).
[0052] Example 2 0.35 mass% potassium coconut oil fatty acid and 1.05 mass% polyvinyl alcohol (saponification degree 74 mol%, viscosity of 4% aqueous solution at 20°C 4.7 mPa·s) were mixed and dissolved in 98.6 mass% water to obtain an anti-fogging agent (2). The fatty acid composition of the coconut oil used in Example 2 is as shown in Table 3 below. Next, using the obtained antifogging agent (2), an antifogging resin sheet (2) and a secondary molded product (2) were obtained in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1. The anti-fogging resin sheet (2) had good sheet appearance, anti-fogging properties, adhesion and antistatic properties, and no water droplet marks were observed after the anti-fogging properties were exhibited.
[0053] Example 3 0.49 mass% sodium laurate, 0.21 mass% potassium oleate, and 0.7 mass% polyvinyl alcohol (saponification degree 74 mol%, viscosity of 4% aqueous solution at 20°C 4.7 mPa·s) were mixed and dissolved in 98.6 mass% water to obtain an anti-fogging agent (3). Next, using the obtained antifogging agent (3), an antifogging resin sheet (3) and a secondary molded product (3) were obtained in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1. The anti-fogging resin sheet (3) had good sheet appearance, anti-fogging properties, adhesion and antistatic properties, and no water droplet marks were observed after the anti-fogging properties were exhibited.
[0054] Example 4 0.35 mass% sodium laurate, 0.35 mass% potassium oleate, and 0.7 mass% polyvinyl alcohol (saponification degree 74 mol%, viscosity of 4% aqueous solution at 20°C 4.7 mPa s) were mixed and dissolved in 98.6 mass% water to obtain an anti-fogging agent (4). Next, using the obtained antifogging agent (4), an antifogging resin sheet (4) and a secondary molded product (4) were obtained in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1. The anti-fogging resin sheet (4) had good sheet appearance, anti-fogging properties, adhesion and antistatic properties, and no water droplet marks were observed after the anti-fogging properties were exhibited.
[0055] Example 5 An anti-fogging agent (5) was obtained in the same manner as in Example 1, except that sodium laurate was changed to potassium laurate. Next, using the obtained antifogging agent (5), an antifogging resin sheet (5) and a secondary molded product (5) were obtained in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1. The anti-fogging resin sheet (5) had good sheet appearance, anti-fogging properties, adhesion, and antistatic properties, and no water droplet marks were observed after the anti-fogging properties were exhibited.
[0056] Comparative Example 1 A comparative anti-fogging agent (1) was obtained by mixing and dissolving 0.21 mass% of sucrose laurate (monoester 70%, HLB 15), 0.35 mass% of polyvinyl alcohol (saponification degree 74 mol%, viscosity of 4% aqueous solution at 20°C 4.7 mPa s) and 0.84 mass% of sodium laurate in 98.6 mass% water. Next, using the obtained comparative antifogging agent (1), a comparative antifogging resin sheet (1) and a comparative secondary molded product (1) were obtained in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2. The comparative anti-fogging resin sheet (1) had good anti-fogging properties, but poor adhesion to the sheet. In addition, in Table 2, since the composition contains 0.21 mass% sucrose laurate, 0.35 mass% polyvinyl alcohol, and 0.84 mass% sodium laurate, the sucrose fatty acid ester (sucrose laurate) is expressed as 0.21 / (0.21+0.35+0.84)=15, the polyvinyl alcohol is expressed as 0.35 / (0.21+0.35+0.84)=25 (mass%), and the sodium laurate is expressed as 0.84 / (0.21+0.35+0.84)=60 (mass%).
[0057] Comparative Example 2 Comparative antifogging agent (2) was obtained in the same manner as in Comparative Example 1, except that the components contained in the antifogging agent were changed to the contents shown in Table 2. Next, using the obtained comparative antifogging agent (2), a comparative antifogging resin sheet (2) and a comparative secondary molded product (2) were obtained in the same manner as in Comparative Example 1, and evaluated in the same manner as in Example 1 and Comparative Example 1. The evaluation results are shown in Table 2. In addition, Comparative Example 1 has an antifogging agent composition corresponding to Example 1 of Patent Document 1, and Comparative Example 2 has an antifogging agent composition corresponding to Example 3 of Patent Document 1.
[0058] Comparative Example 3 1.6 mass% of sodium oleate and 1.6 mass% of polyvinyl alcohol (saponification degree 74 mol%, viscosity of 4% aqueous solution at 20°C 4.7 mPa·s) were mixed and dissolved in 96.8 mass% of water to obtain a comparative anti-fogging agent (3). Next, using the obtained comparative antifogging agent (3), a comparative antifogging resin sheet (3) and a comparative secondary molded product (3) were obtained in the same manner as in Comparative Example 1, and evaluated in the same manner as in Example 1 and Comparative Example 1. The evaluation results are shown in Table 2.
[0059] [Table 1]
[0060] [Table 2]
[0061] [Table 3]
[0062] The anti-fog resin sheets of the Examples had good sheet appearance, anti-fog properties, and adhesion, and no water droplet marks were observed after the anti-fog properties were exhibited. Furthermore, anti-fog resin sheets containing a fatty acid salt in which the salt type is potassium (especially anti-fog resin sheets containing potassium laurate) showed good results in all aspects of sheet appearance, anti-fog properties, adhesion, prevention of water stains after anti-fog properties have been exhibited, and antistatic properties. On the other hand, the anti-fogging resin sheet of the comparative example containing a sucrose fatty acid ester had good anti-fogging properties but poor adhesion to the sheet.
[0063] As can be seen from the results shown in Table 1, the anti-fog resin sheets obtained in the examples exhibited satisfactory results in all respects, including good sheet appearance, good anti-fog properties, good adhesion, and prevention of water stains.
Claims
1. At least one surface of the thermoplastic resin sheet is The anti-fogging resin sheet has an anti-fogging layer formed thereon, the anti-fogging agent comprising (A) a fatty acid salt including a laurate salt, and (B) at least one selected from polyvinyl alcohol and polyvinylpyrrolidone, but not a sucrose fatty acid ester.
2. The anti-fogging resin sheet according to claim 1 , wherein the laurate is at least one selected from sodium laurate and potassium laurate.
3. The anti-fogging resin sheet according to claim 2 , wherein the laurate is potassium laurate.
4. The anti-fogging resin sheet according to claim 1, wherein the polyvinyl alcohol (B) has a saponification degree of 65 to 90 mol %.
5. 2. The anti-fogging resin sheet according to claim 1, further comprising a release layer made of silicone oil (E) formed on the other surface of said thermoplastic resin sheet opposite to the surface on which the anti-fogging layer is formed.
6. The anti-fog resin sheet according to claim 1 , wherein the thermoplastic resin sheet is a styrene-based resin sheet.
7. A secondary molded product obtained by molding the anti-fogging resin sheet according to any one of claims 1 to 6.
Citation Information
Patent Citations
Anti-fogging styrenic resin sheet and its molded article
JP2008222868A
Cited By
Aqueous dispersion, coating agent, and method for producing same
WO2026058949A1